The Effect of The Prodigy-Assisted Game_Based_Learning Model On Critical Thinking And Interest - hamidah; Wijaya kusuma, Jaka; Junariah (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2024)
This study aims to determine and develop game-based learning assisted by Prodigy game media that is valid, practical and effective on students' critical thinking skills and learning interests. Media is a tool for conveying messages sourced from teachers so that students, as recipients, can understand the material well. Prodigy is an ICT-based media that contains games and mathematics learning, so students' interest in learning mathematics will develop through this media. This research uses ADDIE development techniques. The results showed that game-based learning assisted by Prodigy game media proved valid, practical and effective in improving students' critical thinking skills and learning interests. Using apps like Prodigy Game in math learning helps improve students' critical thinking skills through various interactive and focused ways. It changes their perception of math learning to be more positive and engaging. Keywords: Media Prodigy, Game Based Learning, Critical Thinking, Interest